2019
DOI: 10.3390/foods8090392
|View full text |Cite
|
Sign up to set email alerts
|

Food Safety and Nutraceutical Potential of Caramel Colour Class IV Using In Vivo and In Vitro Assays

Abstract: Nutraceutical activity of food is analysed to promote the healthy characteristics of diet where additives are highly used. Caramel is one of the most worldwide consumed additives and it is produced by heating natural carbohydrates. The aim of this study was to evaluate the food safety and the possible nutraceutical potential of caramel colour class IV (CAR). For this purpose, in vivo toxicity/antitoxicity, genotoxicity/antigenotoxicity and longevity assays were performed using the Drosophila melanogaster model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 62 publications
0
4
0
2
Order By: Relevance
“…in the presence of caramelization promoters (ammonia or ammonium in class III and IV, respectively). The results reported that CAR was neither toxic nor genotoxic and showed antigenotoxic effects in Drosophila [8]. Moreover, caramel showed chemopreventive activity and modified the methylation status of HL-60 cell line.…”
mentioning
confidence: 97%
“…in the presence of caramelization promoters (ammonia or ammonium in class III and IV, respectively). The results reported that CAR was neither toxic nor genotoxic and showed antigenotoxic effects in Drosophila [8]. Moreover, caramel showed chemopreventive activity and modified the methylation status of HL-60 cell line.…”
mentioning
confidence: 97%
“…(2) Combined treatments using standard medium and 0.15 M hydrogen peroxide. (3) Asterisks (*) indicate significant differences (one tail) with respect to the untreated control group and (4) the hydrogen peroxide control group: * Chi-square value higher than 5.02 [ 17 ].…”
Section: Figurementioning
confidence: 99%
“…Toxicity, antitoxicity, genotoxicity, antigenotoxicity and life and healthspan in vivo assays were carried out in order to characterise the safety and nutraceutical potential of CRB, SFRB, TAU and GLU, establishing their effects on larvae viability, somatic mutations and how they affect life expectancy in Drosophila melanogaster model, respectively. Drosophila model organism has been used as a reliable model to evaluate the toxicity, genotoxicity and other degenerative process [ 14 , 15 ] and the Somatic Mutation And Recombination Test (SMART), based on the genetic alterations produced in the cells of imaginal discs of the larvae, has been shown to be able to detect genotoxic activity of various compounds with different chemical structures and complex mixtures [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…To resolve this problem, manufacturers prefer the use of caramel coloring to mask the photodegradation of Monascus pigments. However, caramel coloring alters the original color of HQW and may have negative effects on food safety and human health ( Vollmuth, 2018 ; Mateo-Fernández et al, 2019 ). Thus, the effective and inert stabilizers of Monascus pigments are needed to reduce the photodegradation of HQW during storage, and thus maintain and improve its sensory profile.…”
Section: Introductionmentioning
confidence: 99%